2013
DOI: 10.1017/s1368980013000256
|View full text |Cite
|
Sign up to set email alerts
|

Neural tube defects in Latin America and the impact of fortification: a literature review

Abstract: Objective: Data on the prevalence of birth defects and neural tube defects (NTD) in Latin America are limited. The present review summarizes NTD prevalence and time trends in Latin American countries and compares pre-and post-fortification periods to assess the impact of folic acid fortification in these countries. Design: We carried out a literature review of studies and institutional reports published between 1990 and 2010 that contained information on NTD prevalence in Latin America. Results: NTD prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 48 publications
2
71
3
5
Order By: Relevance
“…Some countries, have not implemented mandatory FA fortification. Numerous epidemiological studies have shown the strategy of fortifying foods with FA has led to a pronounced reduction in neural tube defects (NTD) in many countries (De Wals et al, 2007;Honein, Paulozzi, Mathews, Erickson, & Wong, 2001;Rosenthal et al, 2013). Although mandatory FA fortification of cereal products was first put in place in the US to lower the incidence of NTD, there is a renewed requirement to fortify specifically recognised ethnic food sources in order to prevent racial disparity towards preventing NTD (Hammer & Tinker, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some countries, have not implemented mandatory FA fortification. Numerous epidemiological studies have shown the strategy of fortifying foods with FA has led to a pronounced reduction in neural tube defects (NTD) in many countries (De Wals et al, 2007;Honein, Paulozzi, Mathews, Erickson, & Wong, 2001;Rosenthal et al, 2013). Although mandatory FA fortification of cereal products was first put in place in the US to lower the incidence of NTD, there is a renewed requirement to fortify specifically recognised ethnic food sources in order to prevent racial disparity towards preventing NTD (Hammer & Tinker, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports of waterborne epidemics attest to this-the largest aff ecting more than 400 000 (mostly im muno competent) people. 3 Cryptosporidiosis aff ects young children, 4 and it is well known now to have adverse effects on nutritional outcomes. Growth pledges need to be tracked.…”
Section: Authors' Replymentioning
confidence: 99%
“…Yet, physicians do not sufficiently investigate for Cryptosporidium as a cause of diarrhoea in immunocompetent individuals in India. 3 Despite its…”
Section: Diarrhoea In Children and Cryptosporidiummentioning
confidence: 99%
See 1 more Smart Citation
“…No mundo, a prevalência de DFTN é estimada em mais de 300.000 novos casos por ano, com mais de 40.000 mortes e altas taxas de incapacitação (Rosenthal et al, 2013). No Brasil, são escassas as publicações sobre a prevalência dos DFTN.…”
Section: Deficiência De Folatounclassified